URGENSI PENDIDIKAN ANTIKORUPSI UNTUK HADIR SEBAGAI MATAKULIAH WAJIB BAGI MAHASISWA - Wayan M. Aziz Afifi (Ganesha Civic Education Journal, 2022)
As an effort to overcome and overcome corruption in Indonesia, of course it is not enough just to handle it through legal action against the corrupt perpetrators of the corruption crime. It should be noted that almost every line of life in this nation has acts of corruption which make our country seem to have cultivated corruption as a habit. This of course must be overcome through improving Indonesia's human resources, and the right way to fix this is through anti-corruption education to form anti-corruptive character in each individual. The next generation of the nation must break this culture of corruption and they need to be prepared to deal with acts of corruption that still exist after they take the nation's leadership relay so they are not tempted to corruption but to fight corruption itself. Character and values that are strong and based on Pancasila are the key to inculcating morals that must be owned by everyone, especially students who are the closest intellectual generation that will continue the sustainability of this nation. So it is important to organize anti-corruption education on every campus to become a mandatory subject that must be taken to lead to a generation that is not pro against all forms of corruption.